Dendritic cells in liver transplantation immune response - Du, Xiaodong; Li, Mingqian; Huan, Chen; Lv, Guoyue (Frontiers in Cell and Developmental Biology, 2023)
Dendritic cells (DCs) are the most powerful antigen presenting cells (APCs), they are considered one of the key regulatory factors in the liver immune system. There is currently much interest in modulating DC function to improve transplant immune response. In liver transplantation, DCs participate in both the promotion and inhibition of the alloreponse by adopting different phenotypes and function. Thus, in this review, we discussed the origin, maturation, migration and pathological effects of several DC subsets, including the conventional DC (cDC), plasmacytoid DC (pDC) and monocyte-derived DC (Mo-DC) in liver transplantation, and we summarized the roles of these DC subsets in liver transplant rejection and tolerance. In addition, we also outlined the latest progress in DC-based related treatment regimens. Overall, our discussion provides a beneficial resource for better understanding the biology of DCs and their manipulation to improve the immune adaptability of patients in transplant status.